Podcasts or Vodcasts? Exploring First-Year Students’ Preferences for Enhancing Academic Writing Skills - Mohale, Ntshimane Elphas (Research in Social Sciences and Technology, 2025)
First-year students in a distance learning institution face academic writing challenges arising from inadequate writing skills developed in high school, the need to adapt to new writing standards, and limited language proficiency. These challenges could potentially lead to higher dropout’ rates, increased failures, and delayed qualification completion. Specific writing challenges include producing suitable academic content, adhering to academic writing conventions, using one’s own voice, citation and referencing, and style. To aid these students, podcasts and vodcasts were introduced for a student body of approximately 30,000. Transactional Distance Theory and Community of Inquiry framework underpinned the study. In addition, the study collected data using online open-ended evaluation questions and focus group discussions. Vodcasts gained preference due to their visual-auditory approach, aligning with tech-savvy students’ preferences. Vodcasts effectively improve academic writing by demonstrating concepts visually. Vodcasts reduced transactional distance between students and lecturers, encouraging collaborative learning and reducing the isolation factor. While podcasts were less preferred, they enhanced listening skills and sparked interest in the subject matter. Based on the findings, the study proposed guidelines for impactful vodcast creation, showing vodcasts’ effectiveness in addressing distance learning writing issues, enhancing engagement, collaboration, and understanding.